Distribution of Infections and Bacteriological Spectrum in Crush Syndrome - Ersoy Dursun, Fadime; Gunal, Ali Ihsan; Yildirim, Alpagan Mustafa (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2015)
OBJECTIVE: This research was designed as a therapeutic and prognostic study to assess the clinical and bacteriological examination findings of crush syndrome patients admitted to our hospital after the Bingol earthquake. MATERIAL and METHODS: A retrospective assessment was carried out on the medical records of the patients with Crush syndrome. Sixteen patients were admitted to the nephrology department after the earthquake. The patients had a mean age of 23 +/- 13 years and a mean time spent under rubble of 10.3 +/- 7 hours. A total of 16 fasciotomy procedures were carried out in 16 of 11 cases (68%), while 9 of these cases had surgical wounds complicated by infection. RESULTS: Microbiology tests detected bacteriological agents in 88 of 43 (49%) specimens collected from 16 of 13 (81%) patients. The major bacterial isolates from wound infections included Acinetobacter (46%), Escherichia coli (23%) and coagulase negative Staphylococci (14%). Increased length of hospitalization resulted in supervening of secondary bacterial infections. No patients who received treatment died, however a patient surviving a cardiac arrest later developed ischemic encephalopathy. CONCLUSION: Infections are a major problem in crush syndrome, but we suggest that early and vigorous care and appropriate prophylactic antibiotic treatment play a key role in decreased mortality.
Keywords: Infections; Crush syndrome; Prophylactic antibiotic